Pendidikan Agama Kristen Transformatif: Kunci Pembentukan Karakter dan Pertumbuhan Rohani Siswa - Sandra Rosiana Tapilaha (Sekolah Tinggi Alkitab Jember, 2025)
A holistic approach allows for the integration of Christian values into daily life, so that students not only understand religious doctrine theoretically, but also experience and apply it in real life. In addition, the integration of technology and digital media in religious education is an effective means of increasing student engagement, especially for Generation Alpha, who are growing up in a digital environment. The application of active participation-based spiritual discipline also serves as the foundation for continuous spiritual growth, where students are invited to experience faith in a tangible way through Bible reflection, communal prayer, and involvement in social service. This study employs a qualitative method, combining literature reviews from various sources, including book libraries and other academic research. Data was analyzed descriptively to evaluate the effectiveness of the holistic approach in Christian religious education. The results of the study show that it significantly improves students' understanding and experience of faith. The conclusion of this study affirms that transformative Christian religious education must accommodate these various aspects in order to shape individuals who not only have strong religious knowledge but are also able to apply these values in their lives. Pendekatan holistik memungkinkan integrasi nilai-nilai kristiani dalam kehidupan sehari-hari, sehingga siswa tidak hanya memahami doktrin agama secara teoretis, tetapi juga mengalami dan menerapkannya dalam tindakan nyata. Selain itu, integrasi teknologi dan media digital dalam pembelajaran agama menjadi sarana yang efektif untuk meningkatkan keterlibatan siswa, terutama Generasi Alpha yang tumbuh dalam lingkungan digital. Penerapan disiplin spiritual berbasis partisipasi aktif juga menjadi fondasi bagi pertumbuhan rohani yang berkelanjutan, di mana siswa diajak untuk mengalami iman secara nyata melalui refleksi Alkitab, doa bersama, dan keterlibatan dalam pelayanan sosial. Penelitian ini menggunakan metode kualitatif, yang menggabungkan studi literatur dari berbagai sumber, termasuk perpustakaan buku dan penelitian akademik lainnya. Data dianalisis secara deskriptif untuk mengevaluasi efektivitas pendekatan holistik dalam pendidikan agama Kristen. Hasil penelitian menunjukkan bahwa secara signifikan meningkatkan pemahaman dan pengalaman iman siswa. Kesimpulan dari penelitian ini menegaskan bahwa pendidikan agama Kristen yang transformatif harus mengakomodasi berbagai aspek ini agar dapat membentuk individu yang tidak hanya memiliki pengetahuan agama yang kuat, tetapi juga mampu menerapkan nilai-nilai tersebut dalam kehidupan mereka.